1873 Ga. Code 826 - (:unkn) unknown (My University, 1873)
§ 4580: Prohibited hunting any kind of game with gun or dogs, or both, on the day of the Sabbath. Violators guilty of a misdemeanor.
Keywords: HUNTING REGULATION